Analisis Pengaruh Fleksibilitas Kerja Dan Pendapatan Dosen Terhadap Kinerja Dosen Studi Kasus Di Kampus IT&B Medan - Susanto, Agus (JURNAL EKUIVALENSI, 2024)
The objective of this study is to examine the impact of work flexibility and employee compensation on the performance of lecturers at the IT&B Medan Campus. Flexibility is crucial in education, particularly when managing the requirements of the digital era, which enables the use of more adaptive work approaches. The remuneration of employees is a pivotal element that may significantly influence an individual's drive and productivity. This study employed a survey approach to distribute questionnaires to professors at the IT&B Medan Campus. We performed a comprehensive examination of the collected data using multiple linear regression to explore the relationship between job flexibility, income, and employee performance. The study results indicate that the ability to have flexible work arrangements has a significant and positive effect on the performance of lecturers. In addition, employee remuneration also has a significant impact, albeit its scale is relatively lower compared to that of work flexibility. These findings offer educational institution management useful insights into developing policies that encourage work flexibility and improve employee well-being, eventually resulting in optimal performance.